Behavioral and Neural Activity-Dependent Recanalization of Plugged Capillaries in the Brain of Adult and Aged Mice - Reeson, Patrick; Schager, Ben; Van Sprengel, Myrthe; Brown, Craig E. (Frontiers in Cellular Neuroscience, 2022)
The capillaries of the brain, owing to their small diameter and low perfusion pressure, are vulnerable to interruptions in blood flow. These tiny occlusions can have outsized consequences on angioarchitecture and brain function; especially when exacerbated by disease states or accumulate with aging. A distinctive feature of the brain’s microvasculature is the ability for active neurons to recruit local blood flow. The coupling of neural activity to blood flow could play an important role in recanalizing obstructed capillaries. To investigate this idea, we experimentally induced capillary obstructions in mice by injecting fluorescent microspheres and then manipulated neural activity levels though behavioural or pharmacologic approaches. We show that engaging young adult and aged mice with 12 hours exposure to an enriched environment (group housing, novel objects, exercise wheels) was sufficient to significantly reduce the density of obstructed capillaries throughout the forebrain. In order to more directly manipulate neural activity, we pharmacologically suppressed or increased neuronal activity in the somatosensory cortex. When we suppressed cortical activity, recanalization was impaired given the density of obstructed capillaries was significantly increased. Conversely, increasing cortical activity improved capillary recanalization. Since systemic cardiovascular factors (changes in heart rate, blood pressure) could explain these effects on recanalization, we demonstrate that unilateral manipulations of neural activity through whisker trimming or injection of muscimol, still had significant and hemisphere specific effects on recanalization, even in mice exposed to enrichment where cardiovascular effects would be evident in both hemispheres. In summary, our studies reveal that neural activity bi-directionally regulates the recanalization of obstructed capillaries. Further, we show that stimulating brain activity through behavioral engagement (ie. environmental enrichment) can promote vascular health throughout the lifespan.